Potential Benefit of Intra-operative Administration of Ketorolac on Breast Cancer Recurrence According to the Patient's Body Mass Index. (30th April 2018) - Desmedt, Christine; Demicheli, Romano; Fornili, Marco; Bachir, Imane; Duca, Mariana; Viglietti, Giulia; Berlière, Martine; Piccart, Martine; Sotiriou, Christos; Sosnowski, Maurice; Forget, Patrice; Biganzoli, Elia
Abstract: Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are currently used in some countries as analgesics in primary cancer surgery. Retrospective studies suggest that NSAIDs could reduce breast cancer recurrences. Because NSAIDs also act on biological mechanisms present in patients with increased adiposity, we aimed at assessing whether the intra-operative administration of ketorolac or diclofenac would be associated with a reduction of recurrence in patients with elevated body mass index (BMI). Methods: We considered two institutional retrospective series of 827 and 1007 patients evaluating the administration of ketorolac (n = 529 with, n = 298 without) or diclofenac (n = 787 with, n = 220 without). The BMI subgroups were defined as less than 25 kg/m 2 (lean) and 25 or more kg/m 2 (overweight and obese). Cumulative incidence estimation of distant metastases as well as Fine-Gray and Dixon-Simon models was used. These analyses were adjusted for clinico-pathological variables. All statistical tests were two-sided. Results: The administration of ketorolac was statistically significantly associated with decreased incidence of distant recurrences (adjusted hazard ratio [aHR]= 0.59, 95% confidence interval [CI] = 0.37 to 0.96, P = .03). In particular, the association was evident in the high–body mass index (BMI) group of patients (aHR = 0.55, 95% CI = 0.31 to 0.96, P = .04). The administration of diclofenac was not statistically significantly associated with decreased incidence of distant recurrences, either in the global population or in the BMI subgroups. Conclusions: These results show that the intra-operative administration of ketorolac, but not diclofenac, is statistically significantly associated with a reduction of distant recurrences in patients with increased BMI. Altogether, this study points to a potentially important repositioning of ketorolac in the intra-operative treatment of patients with elevated BMI that, if prospectively validated, might be as impactful as and cheaper than adjuvant systemic anticancer therapies.